2010
DOI: 10.1002/hed.21264
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular free flap reconstruction versus palatal obturation for maxillectomy defects

Abstract: Moderate-sized maxillectomy defects involving the palate can be successfully treated with either an obturator or free flap reconstruction. Extensive defects have a better functional outcome with free flaps. Evidence does not suggest that free flap reconstructions delay diagnosis of local recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
145
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 27 publications
(41 reference statements)
4
145
0
2
Order By: Relevance
“…Moreno et al reported that moderately sized maxillectomy defects involving the palate can be successfully treated with either an obturator or free flap reconstruction; however, extensive defects have a better functional outcome with free flaps [10]. In our case, bony reconstruction and insertion of a dental implant should have been performed because the maxillary defect was relatively extensive and our patient was relatively young.…”
Section: Discussionmentioning
confidence: 82%
“…Moreno et al reported that moderately sized maxillectomy defects involving the palate can be successfully treated with either an obturator or free flap reconstruction; however, extensive defects have a better functional outcome with free flaps [10]. In our case, bony reconstruction and insertion of a dental implant should have been performed because the maxillary defect was relatively extensive and our patient was relatively young.…”
Section: Discussionmentioning
confidence: 82%
“…7 Reconstruction mainly depends on the placement of palatal obturators and/or free flaps with microvascular anastomosis, which are harvested from a distant donor site, which in turn increases the morbidity and need for additional surgical intervention. 10,11 Palatal obturators are frequently used to treat small and medium size defects, and they represent the 'gold standard' technique in terms of functional restoration without the need for additional surgery. However, the prostheses can be problematic because of prolonged maintenance, and they are particularly inconvenient for people with poor manual dexterity or visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…This requires selection of an appropriate flap, in which mobile bone, muscle and skin elements are used to reconstruct the alveolar process of the maxilla, the zygomatic arch, the lateral wall of the nasal cavity, the palate and/or the cheek. Free bone flaps meet these requirements (6,7). Depending on the volume of resected soft tissue and the extent of bone resection, the free fibula or iliac crest flap are selected (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%